Estudio de credibilidad de los medios de comunicación desde las perspectivas de las audiencias locales, zona sur de Los Ríos - Tenesaca Cuzco, Narcisa del Rosario (2019)
The media today play a fundamental role in the life of society. For this reason the need to know the opinion generated by the different means of communication existing in the environment, by the citizens is evidenced. By directing this work within the southern area of Los Ríos, it allows to know not only the point of view of a certain sector, but rather to know the opinion of several people from different places, where each one will make clear the perspective they maintain of the media. For the realization of this work, the well-known surveys have been implemented, developed in all the Cantons belonging to the southern area of Los Ríos, in order to finish the degree of credibility generated by the media in people at the time of report. The importance of knowing the degree of credibility that the media maintains before the eyes of the citizenship is contemplated, since this allows having a clearer knowledge, about the quality of the journalistic work developed in the southern zone, the credibility that the Communicators maintain, and the favorable or unfavorable opinion that citizens hold of each one of them